Challenges of Government Accounting Policy Reform in Indonesia - Gracia Maya Kristiani; Rodiyatul Fadillah; Sahrul Sahrul; Silvia Ayu Anggraeni (University of Merdeka Malang, 2024)
This article delves into the significant changes in government accounting, particularly in Indonesia. The shift from cash-based accounting to accruals, and ultimately to full accruals, marks a significant transformation in the country’s government accounting practices. The research methodology employed in this study is a qualitative approach to a literature review. The primary source of information was a comprehensive search of publications about accounting regulations implemented by the government. The main objective of this study is to identify and evaluate the challenges faced during the reform of Indonesia’s government accounting policy. The study’s findings reveal that the government is required to prepare financial accounts under Law No. 17 Year 2003. This law refers to the Government Accounting Standards (SAP). As a derivative of this regulation, the government enacted Government Regulation Number 24 of 2005. This regulation has been revised with Government Regulation Number 71 of 2010 on Government Accounting Standards (SAP). The practical implication of these regulations is a significant change in the basis of government accounting records. Previously, the records were maintained on a cash basis, accrual basis, and cash basis. However, with the new regulations, the records are now maintained on a fully accrual basis. This change is expected to improve the transparency and accuracy of government financial records, thereby enhancing public trust in government financial management. In conclusion, the transition to full accrual accounting is a notable development in Indonesian government accounting. Despite the challenges, this transition is a crucial step toward improving the quality and reliability of government financial information. The study provides valuable insights into the obstacles encountered during this reform and offers recommendations for future policy improvements.